Presence of Antibiotic-Resistant in Staphylococcal Subclinical Mastitis in Several Regencies of East Java, Indonesia - D. C. Widianingrum; H. Khasanah; H. S. Addy (Faculty of Animal Science, Bogor Agricultural University, 2022)
Staphylococcal mastitis has been reported as a serious dairy disease in various regions around the world. The occurrence of resistant strains in Staphylococcus species to antibiotics has triggered alternative treatment substituting antibiotic usage on the global scene. This study aimed to investigate the presence of antibiotic-resistant genes in Staphylococcal subclinical-mastitis cases present in several regencies of East Java Province, Indonesia. A total of 592 quarter milk samples were collected from 62 farms in the region with high dairy cattle populations in Lumajang, Banyuwangi, Malang, Sidoarjo, Jember, Pasuruan, Probolinggo, and Mojokerto. Subclinical-mastitis samples were screened using the California mastitis test (CMT). Positive CMT samples were grown on the selective Staphylococcus media and tested for their biochemical properties. The polymerase chain reaction was performed to detect the presence of antibiotic-resistant genes in all isolates (Staphylococcus sp) using a specific pair-primer for mecA, blaZ, tetK, and tetM genes. The result showed that about 67% of milk samples were subclinical mastitis in several regencies of East Java. About 17.12% of subclinical mastitis was caused by Staphylococcus species (Staphylococcus aureus, Staphylococcus epidermidis, and other non-aureus Staphylococci (NAS)). The most prevalent region of Staphylococcal subclinical-mastitis was recorded in Jember. However, only NAS species obtained from Mojokerto, Malang, Probolinggo, and Banyuwangi were detected to have a blaZ gene responsible for penicillin resistance. In conclusion, the appearance of the antibiotic-resistant gene in NAS species found in several regencies of East Java can be used as important information to evaluate Staphylococcal subclinical-mastitis treatment.